Spinal Intradural, Extramedullary Ependymoma with Astrocytoma Component: A Case Report and Review of the Literature - Gene M. Weinstein; Knarik Arkun; James Kryzanski; Michael Lanfranchi; Gaurav K. Gupta; Harprit Bedi (Case Reports in Pathology)
Ependymomas are common spinal lesions, with the vast majority arising in an intramedullary location. Several cases have been described in the literature of ependymomas in an intradural, extramedullary location. The authors present a case of a 56-year-old female who presented with several weeks of lower back pain and weakness. MRI revealed an intradural, extramedullary enhancing mass at L1-L2. The mass was successfully resected surgically. Pathologic evaluation revealed a low grade glioma with components of both ependymoma and pilocytic astrocytoma with MUTYH G382D mutation. Extramedullary ependymomas are very rare tumors. To the authors’ knowledge, this is the first case of ependymoma/astrocytoma collision tumors described in an extramedullary location.